Traditional medicinal plants used for respiratory disorders in Pakistan: a review of the ethno-medicinal and pharmacological evidence - Alamgeer; Waqas Younis; Hira Asif; Amber Sharif; Humayun Riaz; Ishfaq Ali Bukhari; Asaad Mohamed Assiri (BMC, 2018)
Abstract Respiratory disorders are a common cause of malady and demise in Pakistan due to its remoteness, cold and harsh climatic conditions as well as scarce health care facilities. The people rely upon the indigenous plant resources to cure various respiratory disorders. The primary objective of this review was to assemble all available ethno-medicinal data of plants used for respiratory disorders in Pakistan. Pharmacological activity of these plants (based upon published scientific research), distribution, diversity, use, preparation methods, economical value, conservation status and various available herbal products of some plants have also been explored. This study scrutinized various electronic databases for the literature on medicinal plants used in Pakistan to treat respiratory disorders. A total of 384 species belonging to 85 families used to treat respiratory disorders in Pakistan has been documented. Cough was the disorder treated by the highest number of species (214) followed by asthma (150), cold (57) and bronchitis (56). Most of the plants belongs to Asteraceae (32) and Solanaceae family (32) followed by moraceae (17), Poaceae (13), and Amaranthaceae (13) with their habit mostly of herb (219) followed by Shrub (112) and tree (69). Traditional healers in the region mostly prepare ethno medicinal recipes from leaves (24%) and roots (11%) in the form of decoction. Among the reported conservation status of 51 plant species, 5 were endangered, 1 critically endangered, 11 vulnerable, 14 rare, 16 least concern, 3 infrequent and 1 near threatened. We found only 53 plants on which pharmacological studies were conducted and 17 plants being used in herbal products available commercially for respiratory disorders. We showed the diversity and importance of medicinal plants used to treat respiratory disorders in the traditional health care system of Pakistan. As such disorders are still causing several deaths each year, it is of the utmost importance to conduct phytochemical and pharmacological studies on the most promising species. It is also crucial to increase access to traditional medicine, especially in rural areas. Threatened species need special attention for traditional herbal medicine to be exploited sustainably.